STUDI PEMANFAATAN BUAH API-API DALAM PEMBUATAN PEKTIN MENGGUNAKAN METODE LAMA EKSTRAKSI - M janrigo hidayat Hidayat; Raswen Efendi; Yossie Kharisma Dewi (Fakultas Pertanian Universitas Riau, 2025)
The development of alternative pectin sources is important to enhance the utilization of local raw materials. Api-api fruit has potential as a source of pectin that can be optimized through an appropriate extraction process. This study aimed to determine the optimal extraction time for producing pectin from api-api fruit in accordance with established quality standards. The research was conducted experimentally using a Completely Randomized Design (CRD) consisting of five treatment levels with three replications, resulting in a total of fifteen experimental units. The treatments applied were P1 with an extraction time of 70 minutes, P2 with 80 minutes, P3 with 90 minutes, P4 with 100 minutes, and P5 with 110 minutes. The data obtained were statistically analyzed using Analysis of Variance (ANOVA). If the calculated F-value was greater than or equal to the F-table value, the analysis was continued with Duncan’s Multiple Range Test (DMRT) at a 5% significance level. The results showed that the best treatment for api-api fruit pectin extraction was 110 minutes, which had a significant effect on yield, moisture content, and methoxyl content, but no significant effect on ash content. This treatment met the quality standards established by the International Pectin Producers Association (IPPA), with a yield of 7.43%, moisture content of 0.93%, ash content of 5.39%, and methoxyl content of 12.63%.